Prevalence and Significance of Hypermetabolic Lymph Nodes Detected by 2-[18F]FDG PET/CT after COVID-19 Vaccination: A Systematic Review and a Meta-Analysis - Giorgio Treglia; Marco Cuzzocrea; Luca Giovanella; Luigia Elzi; Barbara Muoio (Pharmaceuticals, 2021)
Recently, several articles reported incidental findings at 2-[18F]FDG PET/CT in patients who have received COVID-19 vaccinations, including hypermetabolic axillary lymph nodes (HALNs) ipsilateral to the COVID-19 vaccine injection site which may cause diagnostic dilemmas. The aim of our work was to calculate the prevalence of this finding. A comprehensive computer literature search of PubMed/MEDLINE, Embase, and Cochrane library databases was performed to identify recently published articles that investigated the prevalence of HALNs detected by 2-[18F]FDG PET/CT after COVID-19 vaccination. Pooled prevalence of this finding was calculated through a meta-analytic approach. Nine recently published articles including 2354 patients undergoing 2-[18F]FDG PET/CT after recent COVID-19 vaccination have been included in the systematic review. Overall, HALNs ipsilateral to the vaccine injection site were frequent findings mainly due to vaccine-related immune response in most of the cases. The pooled prevalence of HALNs after COVID-19 vaccination was 37% (95% confidence interval: 27–47%) but with significant heterogeneity among the included studies. Physicians must be aware and recognize the significant frequency of HALNs at 2-[18F]FDG PET/CT related to immune response to vaccine injection. Larger studies are needed to confirm the findings of this systematic review and meta-analysis.